2021
DOI: 10.20473/fmi.v57i1.16733
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between High Sensitivity-C Reactive Protein Level and Impaired Cognitive Function in HIV Patients

Abstract: Human Immunodeficiency Virus (HIV) infection was one of the most serious health challenges in the world. The Ministry of Health of the Republic of Indonesia reports the number of HIV cases in Indonesia as of June 2019 as many as 349,882. At present, although antiretroviral combination therapy has been found, the prevalence of neurocognitive disorders in the form of HIV-associated neurocognitive disorders (HAND) reaches 50% of HIV patients. This study aimed to determine the relationship between high sensitivity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…The internal brain tissues of patients with AD are associated with unconventional protein deposition reactions, which mainly include extracellular amyloid polypeptide deposition and intracellular nerve fiber tangle reaction [ 12 ]. The research materials showed that [ 13 ], in AD, inflammation occurs in the lobes and hippocampus of the brain, resulting in age-like blotches. In addition, the activation of microglia and astroglia in the brain plays a certain role in the occurrence and development of AD in patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The internal brain tissues of patients with AD are associated with unconventional protein deposition reactions, which mainly include extracellular amyloid polypeptide deposition and intracellular nerve fiber tangle reaction [ 12 ]. The research materials showed that [ 13 ], in AD, inflammation occurs in the lobes and hippocampus of the brain, resulting in age-like blotches. In addition, the activation of microglia and astroglia in the brain plays a certain role in the occurrence and development of AD in patients.…”
Section: Discussionmentioning
confidence: 99%
“…e research materials showed that [13], in AD, inflammation occurs in the lobes and hippocampus of the brain, resulting in age-like blotches. In addition, the activation of microglia and astroglia in the brain plays a certain role in the occurrence and development of AD in patients.…”
Section: Discussionmentioning
confidence: 99%
“…HIV infection results from one of two similar retroviruses (HIV-1 and HIV-2) that destroy CD4 + lymphocytes and impair cell-mediated immunity, affecting multiple organ systems 1 , 2 . HIV infection is associated with a two-fold to 10-fold increased risk of venous thrombosis compared with a general population of the same age.…”
Section: Introductionmentioning
confidence: 99%